Fitting competing risks data to bivariate Pareto models. Issue 5 (4th March 2019) - Shih, Jia-Han; Lee, Wei; Sun, Li-Hsien; Emura, Takeshi
ABSTRACT: This paper revisits two bivariate Pareto models for fitting competing risks data. The first model is the Frank copula model, and the second one is a bivariate Pareto model introduced by Sankaran and Nair (1993 ). We discuss the identifiability issues of these models and develop the maximum likelihood estimation procedures including their computational algorithms and model-diagnostic procedures. Simulations are conducted to examine the performance of the maximum likelihood estimation. Real data are analyzed for illustration.